Strategi Pembelajaran Mandiri - Suciyati, Nirwana; Rama, Bahaking (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
The equality education learning process based on the organizer's guidelines is carried out through face-to-face, tutorial and independent patterns. Independent learning strategies are becoming increasingly relevant in the modern educational world, where demands for independence and individual learning initiative are increasing. Independent learning is not learning alone, but learning with encouragement within oneself, whether done in groups. This writing aims to find out more about independent learning strategies. The method used in this writing is literature review. This literature review is a method used to collect various information on topics relevant to the research being discussed. Information gathering can be done through library books to obtain data and from Google Scholar by describing independent learning strategies.